Wireless sensor networks protocols, applications, and network-on-chip communications - Ompal, Ompal; Kumar, Niraj; Mishra, Vishnu Mohan; Kumar, Adesh (Institute of Advanced Engineering and Science, 2024)
A wireless sensor network (WSN) is a network consisting of self-governing sensors that are deployed in space and communicate with each other using wireless technology to monitor physical or environmental variables. These networks generally include compact, inexpensive sensor nodes equipped with sensing, processing, and communication functionalities. WSNs are specifically engineered to gather data from their immediate environment, do local data processing, and subsequently communicate pertinent information either to a central hub or to other interconnected nodes within the network. Continuous research in the domain of WSNs is devoted to advancing security concerns, developing novel sensing technologies, and optimizing communication protocols. The advancements in these domains enhance the ongoing development and efficiency of WSNs. The WSNs are very important for getting information from the real world in many situations. WSNs are flexible tools for keeping an eye on and controlling different environments because they have sensor nodes, wireless communication, and distributed processing. WSNs use network-on-chip (NoC) communication architecture to connect sensor nodes. The article explains the introduction to WSN, the background of wireless communication, motivation, ZigBee protocol, and WSN applications.